Electrochemical studies of gold bioaccumulation by yeast cell wall components - Lack, Barbara Anne (Rhodes University, Faculty of Science, Department of Chemistry, 1999)
Gold, amongst other group 11 metals, was almost certainly one of the first three metals known to man. In addition to the economic importance of the metal, gold has a wide variety of applications in the medical, electrocatalytical and micro-electronics fields. However, the determination of gold ions in solution, with accuracy, precision, sensitivity and selectivity is still an interesting and much debated topic in analytical chemistry. A system whereby gold ions have been successfully detected employing an electrochemical technique, known as stripping voltammetry, has been developed. The electrochemical method was chosen over other available techniques for the sensitivity, particularly at low concentrations, and selectivity properties; notably in the presence of other metal ions. Under acidic conditions, the electrochemical technique was applied and the presence of gold(III), at a concentration of 2.53 x 10â »â µ mol dmâ »Â³ in a mine waste water sample, was detected. Biomass, in particular yeast and algal types, have been successfully employed in extracting low concentrations of gold ions from industrial effluents. The manipulation of the biological facility for mineral interaction, biohydrometallurgy, may yield numerous potential new technologies. South Africa in particular would benefit from this area of research, since the country is a major ore and metal refining country and if the output and the efficiency of the mines could be improved, even by a small percentage, the financial rewards would be vast. In this study, the application of adsorptive cathodic stripping voltammetry (AdCSV) of gold(III) in the presence of various Saccharomyces cerevisiae cell wall components, was investigated to determine which, if any, were involved specifically in the chemical binding of the gold ions. The chitin and mannan extracts showed the most promise with detection limits of 1.10 x 10â »â ¶ mol dmâ »Â³ and 9 x 10â »â ¹ mol dmâ »Â³, respectively; employing the AdCSV technique. A modification of the stripping voltammetry technique, Osteryoung square wave stripping voltammetry (OSWSV), provided the lowest detection limit, for gold(IIl) in the presence of mannan, of 1.70 x 10â »Â¹Â¹ mol dmâ »Â³ ; utilising a modified carbon paste electrode. The detection of gold(III) has been shown to be dependent on the type of electrode employed, the electrolyte solution and the presence of interfering agents. The effect of copper(II) and silver(I) on the detection of the gold(III) in solution was investigated; whilst the silver(I) has shown no detrimental effects on gold (III) detection systems, copper(II) has indicated the possibility of forming an inter-metallic compound with the gold(III). However, mannan has shown to selectively and preferentially bind the gold(III) in the presence of a ten-fold excess of copper(II). Nuclear magnetic resonance (NMR) and infrared (IR) spectroscopy, as well as computer modelling techniques were employed to further investIgate the mannan-gold(III) interaction and proposed complex formed. The NMR, IR and computer modelling data are in agreement with the electrochemical data on proposing a mannan-gold(III) complex. The co-ordination site was established to be in the vicinity of the H-I and H-2 protons and the gold(III) adopts a square-planar geometry upon co-ordination. The benefits of the research are useful from a biological perspective (i. e. as more is known about the binding sites, microbiologists/biochemists may work on the optimisation of parameters for these sites or work could be furthered into the enhanced expression of the sites) and an industrial one. In addition to the' two major benefits, an improved understanding of gold and its chemistry would be achieved, which is advantageous for other fields of research as well.
Keywords: Hydrometallurgy; Electrochemical analysis; Gold ores; Gold